Event-specific impact test protocol for ice hockey goaltender masks - Clark, J. M.; Hoshizaki, T. B.; Gilchrist, M. D. (Sports Biomechanics, 2020)
Goaltenders in the sport of ice hockey are at high risk for concussions from falls to the ice, player collisions and puck impacts. However, current methods used to certify helmets only consider head accelerations for drop tests which may not describe all common injury mechanisms relating to concussion. The purpose of this study was to describe the characteristics of 3 events associated with concussions for ice hockey goaltenders. A helmeted medium National Operating Committee on Standards for Athletic Equipment (NOCSAE) headform was impacted under conditions representing 3 injury events. Three impact locations` velocities were selected for each event based on video analysis of real-world concussive events. Peak resultant linear acceleration, rotational acceleration and rotational velocity of the headform were measured. The University College Dublin Brain Trauma Model (UCDBTM) was used to calculate maximum principal strain (MPS) and von Mises stress in the cerebrum. Each impact event produced a unique dynamic response and brain stress and strain values. This demonstrates that a single impact event (i.e. falls) cannot adequately describe all impact events. As a result, impact protocols which assess multiple impact events such as the protocol described in this study should be used to evaluate ice hockey goaltender masks.